Mathematical stereochemistry - Fujita, Shinsaku, 1944- (De Gruyter, 2015)
Chirality and stereogenicity are closely related concepts and their differentiation and description is still a challenge in chemoinformatics. A new stereoisogram approach, developed by the author, is introduced in this book, providing a theoretical framework for mathematical aspects of modern stereochemistry. The discussion covers point-groups and permutation symmetry and exemplifies the concepts using organic molecules and inorganic complexes.
Keywords: Stereochemistry.; Chemistry -- Mathematics.; elektronické knihy; electronic books